The Influence of Video Vlogs in the Wonocolo Bojonegoro Texas Region on Increasing Students' Learning Motivation in The Subject of Social Sciences - Hidayati, Armawati; Sri Setyowati; Mega Prani Ningsih; Iqbal Ainun Najib (International Journal of Geography, Social, and Multicultural Education, 2024)
The aim of this research is to determine how video vlogs in the Wonocolo Bojonegoro Texas area increase student learning motivation in social studies subjects. This research uses quantitative experimental methods. The data collection technique uses a questionnaire. Validity test and reliability test are instrument tests used in this research activity. The research was conducted at Al-Fatimah Middle School, Bojonegoro, involving 30 class VII students. The data analysis techniques used are classical assumption testing, simple linear regression model testing and hypothesis testing. The results of the research show that there is a significant influence between vlog videos on student learning motivation in social studies subjects at Al-Faorotimah Middle School, Bojonegoro. The regression equation is Y= 24.532 + 0.924X. From the termination coefficient test, it is known that there is a vlog effect of 75.3% on student learning motivation in social studies subjects. The hypothesis test obtained significance < 0.05 (0.001 < 0.05), so Ho was rejected. This means that the partial influence of video vlogs in the Texas Wonocolo Bojonegoro region on student learning motivation in social studies subjects is significant.